Stars: properties and life cicle - Silva, Carlos Daniel Caldeira; Binoti, Victor Hugo Nantet; Dilem, Bernardo Brunoro (Cadernos de Astronomia, 2023)
Since humanity's first steps, we have watched these distant celestial bodies with wonder. In this article, we will approach the stars, their main characteristics and also their differences, discussing the variable stars. We will also cover their life cycle, from birth to stellar death. And we will introduce since small white dwarfs to powerful black holes.
Keywords: stars; light curve; variable stars; spectrum; nuclear fusion; neutron stars